কাজী নজরুল ইসলাম : জীবন ও সৃজন - ইসলাম, রফিকুল, ১৯৩৪-; Nazrul Institute (Dhaka, Bangladesh) (ঢাকা : নজরুল ইন্সটিটিউট, 2018)
Articles on the life and works of Kazi Nazrul Islam, 1899-1976, Bengali author.
গ্রন্থপঞ্জিগত নির্দেশিকা (পৃষ্ঠা ৭১১-৭১৭) ও নির্ঘণ্ট অন্তর্ভুক্ত।
ARC
Development Book Agency
In Bengali; includes passages in English.
Keywords: Nazrul Islam, -- Kazi, -- 1899-1976 -- Criticism and interpretation; Bengali literature